Полная энциклопедия женских рукоделий: [перевод с французского] (Правда Востока, 1993)
Экземпляры: ф.15 (1993) / Инвентарный номер: 37096 / Цена: / Сис.шифр: 37.248 / Авт.знак: П 51 / ГРНТИ: 75.35 / ББК: 37.248я2